Dinamika Gerakan Air Di Tanah: Pengaruh Tekstur, Struktur, Dan Kepadatan Bulk - Gulo, Alexius Alan Sulaiman; Gulo, Glory Ningsih Hartati (CV. SINAR HOWUHOWU, 2024)
This study discusses the dynamics of water movement in soil with a focus on the effects of texture, structure, and bulk density on water movement. The study was conducted using an experimental method in the laboratory, using various types of soil with different textures. The results show that soil texture affects infiltration capacity and permeability, while soil structure plays an important role in supporting water flow. Bulk density was also shown to have a significant effect, where soil with lower density showed higher water movement speeds. These findings provide important insights for water resource management and soil conservation.